Mapping groundwater discharge seeps by thermal UAS imaging on a wetland restoration site - Watts, C. Lyn; Hatch, Christine E.; Wicks, Ryan (Frontiers in Environmental Science, 2023)
One of the key metrics of the effectiveness of wetland restoration is whether a restored wetland behaves hydrologically like a natural wetland. Restoration is designed to increase water residence time on the surface of the site in order to capture and process nutrients, mitigate the impact of local flooding, drought, and provide habitat for wetland species abundance and biodiversity. Quantifying the change in groundwater presence at the wetland’s surface will inform future freshwater wetland restorations across New England. The ability to produce a comprehensive map of locations of groundwater discharge over a large area has the potential to provide insight into restoration practice, its success, and its effects on individual seeps over time. Identification, mapping and measurement of groundwater discharge sites have long been a challenge, but new methodologies are developing with the advancement of Unmanned Aerial Systems (UAS). This study uses a UAS mounted thermal infrared camera to map groundwater seeps on a 25 hectare (62-acre) site in Plymouth, Massachusetts before and after it underwent restoration to a freshwater wetland. Using the thermal map, we located and quantified the spatial extent groundwater seeps present pre-restoration, and changes after restoration. The location and size of these seeps shows that existing groundwater seeps were remained immobile through restoration, but their surface expression grew, indicating that restoration removed barriers to surface expression, and successfully increased residence time. This analysis using thermal camera enabled UAS allows for a temporal comparison over large spatial scales and provides insight into restoration impacts to groundwater expression on the surface of post-agricultural wetland sites.